2004
DOI: 10.1007/s00464-003-8928-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of timing of pneumoperitoneum on the inflammatory response

Abstract: These findings suggest that CO2 pneumoperitoneum downregulates the inflammatory response to LPS challenge. Start time of CO2 insufflation does not appear to alter hepatic expression of acute phase genes. The mechanism of alpha2-macroglobulin downregulation does not appear to be due to IL-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…[7][8][9] This effect could be explained by the insufflation of carbon dioxide (CO 2 ) during laparoscopy, as experimental studies have demonstrated that CO 2 may modify the inflammatory response to injury. [10][11][12][13] This effect has also been reported on an experimental model of peritonitis exploring the direct anti-inflammatory effect on the peritoneum itself. 14 To the best of our knowledge, none of these experimental studies reported the effect of CO 2 on bowel epithelium and the underlying mechanism is only partially understood.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…[7][8][9] This effect could be explained by the insufflation of carbon dioxide (CO 2 ) during laparoscopy, as experimental studies have demonstrated that CO 2 may modify the inflammatory response to injury. [10][11][12][13] This effect has also been reported on an experimental model of peritonitis exploring the direct anti-inflammatory effect on the peritoneum itself. 14 To the best of our knowledge, none of these experimental studies reported the effect of CO 2 on bowel epithelium and the underlying mechanism is only partially understood.…”
Section: Introductionmentioning
confidence: 68%
“…The anti‐inflammatory effect of laparoscopy compared to laparotomy has already been reported in several clinical studies, notably in patients with complicated appendicitis 7–9 . This effect could be explained by the insufflation of carbon dioxide (CO 2 ) during laparoscopy, as experimental studies have demonstrated that CO 2 may modify the inflammatory response to injury 10–13 . This effect has also been reported on an experimental model of peritonitis exploring the direct anti‐inflammatory effect on the peritoneum itself 14 .…”
Section: Introductionmentioning
confidence: 88%
“…[31,43] The underlying philosophy of LS is not only to create a minimal access'' surgical environment, but also to be minimally disruptive'' to the patient. [25] In order to reduce these haemodynamic changes it is recommended that the lowest possible inflation pressure is used, with insufflation started at a standard pressure (12)(13)(14)(15) and then the pressure is gradually lowered down as much as possible without compromising the visibility as in the dial-down' approach. [70,82] Some have also advocated releasing gas intermittently during the procedure.…”
Section: Intraperitoneal Pressure (Ipp)mentioning
confidence: 99%
“…During LS the injury related to the wound is reduced, but other components may develop either as a consequence of abdominal wall and peritoneal distension or in relation to the type of the gas used and the dura-tion of the procedure. [13] Animal studies show that intestinal recovery is faster after laparoscopic procedures than the open procedures. [14][15][16][17] Decreased bowel manipulation and associated inflammation are likely the explanations for these findings, although other considerations may include the minimizing exposure of bowel to the hostile, nonphysiologic environment accompanying laparotomy, which may later alter the motility.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Fuentes et al [1] published a study showing a survival benefit for rats with carbon dioxide (CO 2 ) pneumoperitoneum compared with control animals at 48 h, with interleukin-6 (IL-6) levels attenuated using a CO 2 pneumoperitoneum. In 2004, Bachman et al [2] demonstrated that CO 2 insufflation reduces the inflammatory response in rats based on reduced levels of alpha-2 macroglobulin mRNA and beta fibrinogen. Yet another rat model, described in a 2001 paper by Mendoza-Sagaon et al [3] showed that a transient suppression of delayed-type hypersensitivity (DTH) did not occur in animals with a Nissen fundoplication performed laparoscopically using CO 2 pneumoperitoneum compared with open control subjects.…”
Section: The Controversy: Do Meaningful Immunologic Differences Existmentioning
confidence: 99%